Strategi Kepala Sekolah Mewujudkan Kedisiplinan Peserta Didik di MA Al-Ijtihad Danger - Sopian Ansori; Adi Fadli; M Sobry Sutikno (Universitas Islam Negeri Mataram, Indonesia, 2021)
This study aims to explore strategies or tips, tactics in carrying out programs that have been designed by the principal so that they can run smoothly. This research is a field research with a phenomenological qualitative approach, data collection is done with techniques; 1. Observation 2. In-depth interviews with informants. 3. Documents. Data analysis techniques were carried out with Miles and Huberman models in Sugiyono: data collection, data reduction, data display, and conclusion drawing / verification. While the validity test of the data includes: Test data credibility. The research findings show that in realizing the discipline of students at MA Al-Ijtihad Danger, the principal applies a discipline theory that Reisman and Payne put forward in E. Mulyasa, namely self-concept, communication skills, and has consequences. logical and natural consequences (natural and logical consequences), clarification (values clarification), transactional analysis (transactional analysis), reality therapy (reality therapy), integrated discipline (assertive discipline), behavior modification (behavior modification), disciplinary challenges (dare to discipline). This research concludes that the principal has embodied the discipline of students at MA Al-Ijtihad Danger based on the theory presented by Reisman and Payne in E. Mulyasa but there are still problems in applying the discipline, namely the DO (Drop Out) conducted by the principal there should be coaching conducted by the principal for students who violate so they do not do DO. Keywords: Strategy, Principal, Student Discipline Penelitian ini bertujuan untuk mengali strategi atau kiat, taktik dalam menjalankan program-progam yang sudah dirancang oleh kepala sekolah supaya bisa berjalan lancar. Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif fenomenologi, pengambilan data dilakukan dengan tehnik (1). Observasi (2). Wawancara mendalam dengan informan. (3). Dokumentasi. Teknik analisis data dilakukan dengan model Miles dan Huberman: data collection, data reduction, data display, dan conclusion drawing/verification. Sedangkan uji keabsahan data meliputi: Perpanjangan penelitian dan triangulasi. Temuan penelitian menunjukkan bahwa dalam mewujudukan kedisiplinan peserta didik di MA Al-Ijtihad Danger, kepala sekolah menerapkan teori kedisiplinan yang dikemukan oleh Reisman dan Payne dalam E. Mulyasa yaitu konsep diri (self-concept), ketrampilan berkomunikasi (communication skill), memberikan konsekuensi-konsekuensi logis dan alami (natural and logical consequences), klarifikasi nilai (values clarification), analisis transaksional (transactional analysis), terapi realitas (reality therapy), disiplin yang terintegrasi (assertive discipline), modifikasi perilaku (behavior modification), melakukan tantangan kedisiplinan (dare to discipline). Peniliti ini menyimpukan bahwa kepala sekolah sudah mewujudkan kedisiplinan peserta didik di MA Al-Ijtihad Danger dengan berdasarkan teori yang dikemukan oleh Reisman dan Payne dalam E. Mulyasa tetapi masih ada masalah dalam penerapan kedisiplinan tersebut yaitu adanya DO (Drop Out) yang dilakukan kepala sekolah yang seharusnya ada pembinaan yang dilakukan kepala sekolah untuk peserta didik yang melanggar sehingga tidak melakukan DO. Kata Kunci: Strategi, Kepala sekolah, Kedisiplinan Peserta Didik